Case report: angiosarcoma of the pulmonary artery diagnosed as pulmonary artery emboli - Edina Korça; Jad Kanaan; Kálmán Benke; Gábor Veres; Jens Michaelsen; Gábor Szabó (Journal of Cardiothoracic Surgery, 2022)
Abstract Background Angiosarcomas are the most common malignant tumors of the heart and great vessels. Late onset and unspecific symptoms are reasons why a diagnosis is made rather late at a time when most tumors have already metastasized. We report a rare case of an angiosarcoma presenting as pulmonary artery emboli. Case presentation A 66-year-old patient was initially admitted to the hospital with a STEMI. Days later a successful reanimation due to ventricular fibrillation followed. An emboli of the pulmonary artery was diagnosed as the cause and after a lysis therapy the patient was discharged. A few weeks later the patient suffered an episode of absolute arrhythmia. TTE as well as CT-Scan showed an emboli of the pulmonary artery and a pericardial effusion with compression to the right ventricle. Intraoperative findings, showed an infiltrating tumor of the pulmonary artery, the pulmonary valve, the RVOT, the LA and LV. A resection of the tumor from the pulmonary artery, valve and RVOT was carried out. A new pulmonary valve was implanted with the reconstruction of the RVOT and pulmonary artery. Due to LV infiltration, only a palliative surgical approach was possible. Despite an uncomplicated postoperative course, the patient died at home two months later. Conclusion Although a rarity, a tumor of the pulmonary artery should be taken into consideration as a differential diagnosis to pulmonary artery emboli. Development of better diagnostic tools (specific tumor markers) and more effective chemotherapeutic agents is necessary to improve the prognosis of these patients.